PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. TAMBAK ROBIL DENGAN DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING DI KABUPATEN SITUBONDO - Riziq, Arif; Tulhusnah, Lusiana; Ediyanto, Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The role of human resource management is vital in ensuring a company's longevity by upholding and improving the caliber and efficiency of its workforce. The considerable effect of a company's requirement for impactful employees underscores the indispensability of human resources for every business. Organizations inherently possess tactics that impact both their own functioning and their staff. This study aims to scrutinize and validate the impact of human resource management strategies on enhancing employee performance at PT. Tambak Robil. The research encompasses all PT. Tambak Robil employees situated in Situbondo Regency. The sampling method employed is non-probability sampling using the exhaustive sample approach. Analyzing data and assessing hypotheses in this study are conducted using the Smart PLS 3.0 software (Partial Least Squares) alongside a Structural Equation Model. The outcomes of hypothesis testing through the Smart PLS 3.0 application demonstrate that the work environment exerts a noteworthy and positive impact on work discipline, while compensation also significantly bolsters work discipline. Additionally, the work environment substantially contributes to performance improvement, whereas compensation shows a negligible and unfavorable association with performance. Notably, work discipline prominently enhances performance. The results from the indirect effects analysis via Smart PLS 3.0 indicate that the work environment substantially enhances performance by operating through the conduit of work discipline. Similarly, compensation significantly enhances performance by channeling its influence through work discipline.